Principles of Emotions Affecting Learning and Social Learning in Elementary School - Resyi Abdul Gani; Asep Supena (PT. Banjarese Pacific Indonesia, 2025)
This study aims to develop a comprehensive constellation model and identify optimal strategies for strengthening lecturers’ professional commitment in the largest private universities in Bogor. Penelitian ini mengkaji secara mendalam bagaimana emosi dan belajar sosial memengaruhi proses pembelajaran di sekolah dasar melalui perspektif neuropedagogik dan brain‑based learning. A mixed methods approach was used by combining quantitative analysis (meta-analysis of 173 respondents and 47 indicators of NP, EC, OB, MS, BS) and descriptive qualitative analysis using thematic analysis techniques on semi-structured interviews with five elementary school teachers. The meta-analysis results showed a very strong average effect of the latent construct relationship (t(128) = 12.92; p < 0.001; r ≈ 1.00) with almost zero heterogeneity (Qₑ(128) = 1.67; τ² = 0; I² = 0%), and no significant moderating effects were found for all indicators; the partial meta-regression coefficients for all items were very close to zero and the R² value was 0.000. Qualitatively, three main themes emerged: (1) positive emotions as the foundation of learning readiness, (2) social interaction as a reinforcement of meaning formation, and (3) contextual learning that integrates cognitive, emotional, and social dimensions. Although most teachers have not yet mastered the concepts of neuropedagogy and brain-based learning theoretically, they have intuitively implemented its principles through motivation, praise, humor, group work, collaborative projects, and learning experiences relevant to students' real lives. These findings support the latest theory that places emotions and social interactions as the main drivers of brain function in learning (Immordino Yang, 2016; Tyng et al., 2017; Vygotsky, 1978; Jensen, 2008), and emphasizes the importance of strengthening teachers' competence in understanding and designing brain- and emotion-based learning to support the holistic development of elementary school students.